الأثر الناقل لاستئناف حكم محكمة الجنايات - عبد الحميد, عمارة (جامعة الوادي University of Eloued, 2019)
لقد أدخل المشرع الجزائري تعديلات جوهرية على الاجراءات التي تحكم محكمة الجنايات، تجسيدا للتعديل الدستوري الذي كرس مبدأ التقاضي على درجتين في المادة الجزائية، ترتب عنه استحداث محكمة جنايات ابتدائية تصدر أحكاما قابلة للطعن بالاستئناف ذات أثر ناقل، تفصل فيه محكمة جنايات استئنافية بصفتها درجة ثانية في التقاضي، استنادا إلى الاستئناف الدائري، خلافا لما عليه الحال بالنسبة لاستئناف أحكام الجنح والمخالفات، المبني على الاستئناف العالي أو المتدرج، الذي يخول لجهة الاستئناف الحق في التصدي للحكم المستأنف خلافا للاستئناف الدائري، القائم على الأثر الناقل للحكم المستأنف، الذي يترتب عنه عدم التعرض له عند الفصل فيه لا بالتأييد ولا بالتعديل ولا بالإلغاء، وهو الأثر الذي يثير اشكالات اجرائية من حيث التطبيق القضائي. The Algerian legislator has introduced substantial amendments to the provisions governing the Court of Assizes, following the constitutional amendment which enshrined the principal of a double degree of jurisdiction in the penal law. This has, therefore, resulted in the creation of a criminal court of first instance. This latter pronounces judgments which are subject to appeal in cassation and have devolutive effect to be decided on by a second instance court of criminal appeal, according to the circular appeal, and unlike the appeal of misdemeanors and contraventions judgments, based on appellate jurisdiction. This entitles the appellate jurisdiction to address the appealed sentence, contrary to the circular appeal which lies on the devolutive effect of the appealed sentence that raises procedural problems in terms of judicial application.
Keywords: الأثر ; الناقل ; الاستئناف ; التقاضي ; محكمة الجنايات; effect ; devolutive ; appeal ; jurisdiction ; court of assizes